Study of the efficacy of ormeloxifene in abnormal uterine bleeding - Varwatte, Priyanka B.; Fonseca, Michelle (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Abnormal uterine bleeding (AUB) is a diagnosis that does not apply to menorrhagia only, but also includes (menometrorrhagia) excessively prolonged and frequent bleeding. Ormeloxifene (also known as centchroman) is a selective estrogen receptor modulator. This study was conducted to assess the efficacy, safety and compliance of ormeloxifene in the medical management of AUB. Methods: This quasi experimental, one group pre and posttest research design study was conducted among 30 participants in a tertiary care institute in a metropolitan city during January 2016 to June 2017. Patients with AUB were administered with ormeloxifene were advised to follow up one monthly for the first three months and then three monthly follow up for 6 months. Results: The mean age of all the patients was 35.96±5.62 years. There was statistically significant difference of mean hemoglobin, mean endometrial thickness and mean pregnancy-associated breast cancer (PABC) score observed between pre-treatment and 3 months and 6 months of post treatment. Mean hemoglobin concentration was increased while mean endometrial thickness and mean PABC score was decreased as the duration of treatment was increased from 3 months to 6 months. Conclusions: Ormeloxifene is quick acting, effective and appears to be a promising option for the medical management of dysfunctional uterine bleeding. It leads to a significant reduction in menstrual blood loss, a significant rise in hemoglobin concentration and a significant decrease in endometrial thickness with very minimal side effect.